2x(x+3)-3(2x-3)=

Simple and best practice solution for 2x(x+3)-3(2x-3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x(x+3)-3(2x-3)= equation:


Simplifying
2x(x + 3) + -3(2x + -3) = 0

Reorder the terms:
2x(3 + x) + -3(2x + -3) = 0
(3 * 2x + x * 2x) + -3(2x + -3) = 0
(6x + 2x2) + -3(2x + -3) = 0

Reorder the terms:
6x + 2x2 + -3(-3 + 2x) = 0
6x + 2x2 + (-3 * -3 + 2x * -3) = 0
6x + 2x2 + (9 + -6x) = 0

Reorder the terms:
9 + 6x + -6x + 2x2 = 0

Combine like terms: 6x + -6x = 0
9 + 0 + 2x2 = 0
9 + 2x2 = 0

Solving
9 + 2x2 = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 2x2 = 0 + -9

Combine like terms: 9 + -9 = 0
0 + 2x2 = 0 + -9
2x2 = 0 + -9

Combine like terms: 0 + -9 = -9
2x2 = -9

Divide each side by '2'.
x2 = -4.5

Simplifying
x2 = -4.5

Reorder the terms:
4.5 + x2 = -4.5 + 4.5

Combine like terms: -4.5 + 4.5 = 0.0
4.5 + x2 = 0.0

The solution to this equation could not be determined.

See similar equations:

| x^3+-10x+25=0 | | (4v+1)(3+v)=0 | | x^3-10x+26=0 | | 2(x+1)=4x+2 | | 2y-24x=10 | | -2x^2-2x-12=0 | | -2=3y+7 | | -2x-9y=1 | | 36y=1 | | 28+24p=36p | | 2x^3-6x^2-x=0 | | a^3b^2(3a^2b)= | | 6-(3x-6)=7x-9 | | log(7)1= | | Log(x+12)-log(x)=1 | | 9-(2-3)-[3-(5-2)]-[2+(4-3)]= | | 46=3x+2y | | 2x^4-6x^3-x^2+3x=0 | | (3x-12)+11=1+1.5x | | v-5.4=6.9 | | 3p^2=4-11p | | v-2.1=8.31 | | 21+8b=-7(-8b-3) | | 5n^2-3=14n | | tanx=.375 | | -2(w-5)=6w+34 | | -8w+4=-34 | | x+13y=g | | -2(w-5)=6w+4 | | x+13x=y | | 5tan-12=0 | | 9x^1=-17 |

Equations solver categories